Capital Budgeting Theory and Practice: A Review and Agenda for Future Research - Kengatharan, L. (Applied Economics and Finance, 2016)
The main purpose of this research was to delineate unearth lacunae in the extant capital budgeting theory and practice during the last two decades and ipso facto become springboard for future scholarships. Web of science search and iCat search were used to locate research papers published during the last twenty years. Four criteria have been applied in selection of research papers: be an empirical study, published in English language, appeared in peer reviewed journal and full text research papers. These papers were collected from multiple databases including OneFile (GALE), SciVerse ScienceDirect (Elsevier), Informa - Taylor & Francis (CrossRef), Wiley (CrossRef), Business (JSTOR), Arts & Sciences (JSTOR), Proquest ,MEDLINE (NLM), and Wiley Online Library. Search parameters covered capital budgeting, capital budgeting decision, capital budgeting theory, capital budgeting practices, capital budgeting methods, capital budgeting models, capital budgeting tools, capital budgeting techniques, capital budgeting process and investment decision. Thematic text analyses have been explored to analyses them. Recent studies lent credence on the use of more sophisticated capital budgeting techniques along with many capital budgeting tools for incorporating risk. Notwithstanding, it drew a distinction between developed and developing countries. Moreover, factors impinging on choice of capital budgeting practice were identified, and bereft of behavioral finance and event study methodological approach were highlighted. More extensive studies are imperative to build robust knowledge of capital budgeting theory and practice in the chaotic environment. This research was well thought out in its design and contributed by stating the known and unknown arena of capital budgeting during the last two decades. This scholarship facilitates to academics, practitioners, policy makers, and stakeholders of the company.
Keywords: discount rate; capital budgeting tools